The direct NLRP3 inhibitor and Phase 3 small molecule anticancer agent, RRx‐001, protects aged triple transgenic Alzheimer's disease model mice from CNS degeneration and cognitive decline. (20th December 2022) - Reid, Tony; Oronsky, Bryan; Caroen, Scott; Cabrales, Pedro
Abstract: Background: RRx‐001 is an aerospace‐derived, intravenously administered NLRP3‐specific inhibitor with confirmed CNS‐penetrant properties and a favorable safety profile in a Phase 3 clinical trial. It is under investigation as an anticancer agent, a chemoradioprotector for oral mucositis and a prophylactic for acute graft vs. host disease (aGVHD). RRx‐001 has been shown to reduce interleukin‐1β (IL‐1β) production in vivo and to attenuate the severity both of experimental autoimmune encephalomyelitis (EAE), a disease model of multiple sclerosis, and dextran sulfate sodium (DSS)‐induced colitis. Method: In the present study, the neuroprotective effects of 2mg/kg RRx‐001 administration on Alzheimer's Disease (AD), which has been linked to aberrant NLRP3 activation, were evaluated via i.p. injection once weekly for 3 months on aged (21‐24 months old) triple transgenic AD model (3xTg‐AD) mice and control non‐transgenic (NonTg) mice. Result: This sub‐chronic administration of RRx‐001 improved performance on learning and spatial memory tasks and greater risk assessment behavior based on the elevated plus maze test. A significant increase in reduced glutathione and a decrease in lipid peroxidation and amyloid plaque density were also observed in the 3xTg‐AD mice. Conclusion: Together, these findings suggest that RRx‐001 reverses histological hallmarks of AD and protects cognitive and emotional function in aged 3xTg‐AD mice